FULL WAVEFORM INVERSION USING REVERSE TIME MIGRATION AND GOLDEN RATIO - Aparajita, Made Jnanaparama; Pascaloa, M Rafif; Putra, Ahmad Dedi; Naufal, Harish Hartsa (JGE (Jurnal Geofisika Eksplorasi), 2025)
Seismic wave imaging techniques, such as conventional full-waveform inversion (FWI), which utilize numerical solutions of seismic wave equations, can be a valuable tool for estimating high resolution models of complex geological conditions. However, conventional FWI only uses one variable recording to find the minimum misfit in the step length calculation process, unlike the FWI golden ratio, which looks for minimum misfits using the four-variable recording. The method of calculating the four-variable recording continues to be updated until the velocity value from the FWI golden ratio is close to the actual velocity model values. Then, using reverse-time migration (RTM) in this case study is crucial for determining the final results of the velocity value in the FWI golden ratio. RTM takes over as the actual recording and is used in the process of calculating the gradient on this FWI golden ratio. The gradient is then calculated with a step length to get the model update. Using the golden ratio and gradient step length from RTM really helps reduce misfit. The final result, obtained using RTM and the golden ratio in the FWI method, produces an image that resembles the shape of the true synthetic model and yields updated velocity values that are not significantly different from the true velocity values in the synthetic model.